The detainee dilemma: The U.S. debate about the release of prisoners from Guantanamo Bay - Johannes Thimm (Stiftung Wissenschaft und Politik (SWP), 2009)
Ever since President Obama announced that the detention camp at Guantanamo Bay would be closed by 22 January 2010, there has been controversy in the U.S. about what to do with the remaining 229 detainees. Because the President announced the decision to close the camp by executive order without giving any details about its implementation, Congress has been increasingly questioning his plan. The Republicans are using the issue to accuse Obama of weakness in the fight against terrorism. But even the Democrats have conditioned their support of the new policy on Obama's providing a comprehensive strategy for how to deal with the prisoners. This has created a situation in which the plan to close the prison and deal with the detainees in accordance with the rule of law also depends on Obama's obtaining international support for the placement of the detainees
Keywords: 320